The Implementing Activity-Based Costing Technique (ABC) and Its impact on Profitability: A Study of Listed Manufacturing Companies in Jordan - Al-Qudah, Laith Akram Muflih; Al-Hroot, Yusuf Ali Khalaf (International Journal of Economics and Financial Issues, 2017)
The main objective of this study is to investigate and evaluate the effect of implementing the Activity-Based Costing technique (ABC) to the profitability of the manufacturing companies in Jordan. The sample of this study includes 72 observations; these observations are six financial ratios based on the financial statements of 12 industrial companies in Jordan that implemented the ABC technique in the period 2000 to 2011. A four-year average pre and post the implementation of the ABC technique is taken for all technique variables. The profitability ratios are the Return on assets (ROA), Return on investment ratio (ROI), Return on equity (ROE), Gross profit margin (GP), Operating margin ratio (OM), and Net profit margin ratios (ROS). Using a paired t-test in order to test the significance difference between the pre and post implementation of the ABC technique, the results indicate that four financial ratios, namely the OM, ROS, ROA, and ROE ratios increased and improved after the implementation of the ABC technique. The OM and ROA ratios recorded as the highest ratios for 58.33% of the companies in the sample, while the ROS and ROE ratios increased by 50% for the companies in the sample. Furthermore, the GP ratio indicates that most ratios decreased after the implementation of the ABC technique. The ratio deteriorated for 9 companies out of 12 in the GP ratio, which means that 75% of the companies experienced a decrease in the GP ratio after the implementation of the ABC technique. In addition the ROI ratio decreased for 7 companies out of 12. The results also show little evidence suggesting that using the ABC technique improves the company's profitability ratios with a percentage of 47.22% and there is a general decrease in the profitability ratios for companies that implement the ABC technique with a percentage of 52.78%. It can be concluded that there is no significant overall improvement in the profitability ratios of Jordanian manufacturing companies after the implementation of the ABC technique. Keywords: Activity-Based Costing Technique (ABC), Profitability, Jordan. JEL Classifications: L6, M410